A Low Frequency Model for Acoustic Propagation in a 2D Flow Duct: Numerical Computation (Communications in Computational Physics, 2020)
In this paper we study a low frequency model for acoustic propagation in a2D flow duct. For some Mach profile flow, we are able to give a well-posedness theorem. Its proof relies on a quasi-explicit expression of the solution which provides usan efficient numerical method. We give and comment numerical results for particularlinear, tangent and quadratic profiles. Finally, we give a numerical validation of ourasymptotic model.